The Analysis of Conjunction Found in “The Target” Novel by David Baldacci - Antari, Ni Made Rini; Juniartha, I Wayan (Humanis; Vol 28 No 1 (2024)DO - 10.24843/JH.2024.v28.i01.p04, 2024)
Conjunction are crucial for connecting word, phrases, or clauses in a sentence, enhancing coherence and facilitating smooth communication. The aim of this study is to analyze the types and functions of conjunctions in the novel entitled The Target by David Baldacci. The study uses descriptive qualitative method by using theory from Halliday and Hassan with different years. By using the theory of Halliday and Hassan (1976) to analyze the types of conjunctions, and the theory of Halliday and Hassan (1985) to analyze the functions of conjunctions.  .. The result of this study shows that the additive type of conjunction has the highest and most dominant occurrence which is forty-three times (61,5%) in the use of conjunction. Because additive conjunction are more often used in a sentences in novrl such as conjunction “and” and “or”  The abstract is not well organised so it’s hard for me to follow.